ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA HEMOROID DI RUMAH SAKIT BUDI KEMULIAAN KOTA BATAM TAHUN 2023 - Muhammad Rifki; Andi Asda Astiah; Aghnia Hernawati (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: Symptoms of hemorrhoid can happen because of many risk factors such as age, history of hemorrhoid in family, lack of fiber foods consumption, lack of water, history of constipation, wrong habits of defecation and physical activity. The purpose of this research is to know the correlation between many risk factor that can effect the incident of hemorrhoid. Methods: This research was observational analytic study with case control design. Total samples included 72 people. Samples were obtained by purpossive sampling. The primary data obtained by recording the interviews based on questionairre and analyzed using univariate, bivariate with chi-square. Results: The results showed that hemorrhoid more common in person above 45 years old (55,2%), no family history 80.6%, heavy physical activity 58.3%, no history of constipation 63.9%, squatting defecation position 52.8% , and low fiber consumption of 61.1%. The results of this study was that there was a significant relationship between physical activity (p=<0.000), history of constipation (p=<0.000), fiber consumption (p=<0.000), defecation position (p=<0.001), age (p=0.031) against hemorrhoids. And there is no relationship between family history (p=<0.183) and the incidence of hemorrhoids. Conclusion: There is a significant realtionship between fiber consumption, physical activity, defecation position, age, history of constipation with hemorrhoids. There is no relationship between a family history of hemorrhoids and the incidence of hemorrhoids. Keywords: hemorrhoid, constipation, activity